Personnel Management, Especially the Submission of Proposed Rank Increases At the Education and Culture Office of West Sumbawa Regency - Safrudin, Safrudin; Suparman, Suparman; Anwar, Anwar (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study discusses the effect of digitizing platform-based archives of personnel documents on personnel management, especially the submission of proposals for promotion at Dinas Pendidikan Dan Kebudayaan Kabupaten Sumbawa Barat. The submission of proposals for promotion is still carried out conventionally and the number of civil servants in the scope of work of the Education and Culture Office is greater than that of other OPDs, in line with the number of requests for promotion each year. The purpose of this study was to analyze the effect of platform-based digitization of personnel document archives on personnel management, especially the submission of proposals for promotion at Dinas Pendidikan Dan Kebudayaan Kabupaten Sumbawa Barat. This research uses quantitative research. The approach to analyzing second order factors is to use a repeated indicators approach or also known as a hierarchical component model. The population of this study was 237 respondents, and the sample was 218 respondents. Data analysis was carried out using the Partial Least Square (PLS) method using SmartPLS software version 3.2.9. The results showed that the digitization of platform-based personnel document archives was Beta Coefficient = 0.521 or had a strong influence, t-Statistic = 5.889 and p-Value = 0.000 showing a significant influence on personnel management, especially the submission of promotion proposals. It can be concluded that the digitization of platform-based archives of personnel documents has a positive and significant influence on personnel management, especially the submission of promotion proposals at Dinas Pendidikan Dan Kebudayaan Kabupaten Sumbawa Barat.